The Translation of Culture-Bound Elements into Finnish in the Post-War Period - Hagfors, Irma (Meta, 2003)
AbstractCulture-bound elements, such as proper names and food items, not only place the story of a book in a specific culture and period of time, but also imply certain values and create an ambience. These elements also have an effect on how the reader identifies with the story and characters. Thus, it is important to find the most appropriate strategy to translate such elements. This paper considers the Finnish translation (1949) of Kenneth Grahame’s The Wind in the Willows (1908), a multi-layered and allusive children’s book set in Edwardian England, and some other children’s tales translated into Finnish around the same era. The translation of The Wind in the Willows dates back to a period of time when British culture was not yet well known in Finland. The paper argues that certain inconsistencies in the translation of culture-bound elements in the book make it difficult for target text readers to understand its layers of meaning and to identify with the characters. Similar inconsistencies in the translation of culture-bound elements are found in other Finnish translations of children’s books from the same period. The findings may be explained by a limited knowledge of foreign cultures in post-war Finland.